1998
DOI: 10.1017/s0022112097008033
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the flow of a fluid through a flexible tube at intermediate Reynolds number

Abstract: The stability of the flow of a fluid in a flexible tube is analysed over a range of Reynolds numbers 1<Re<104 using a linear stability analysis. The system consists of a Hagen–Poiseuille flow of a Newtonian fluid of density ρ, viscosity η and maximum velocity V through a tube of radius R which is surrounded by an incompressible viscoelastic solid of density ρ, shear modulus G and viscosity ηs in the region R<r<HR. In the intermediate Reynolds number regime, the stability depends on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
91
5

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(108 citation statements)
references
References 21 publications
12
91
5
Order By: Relevance
“…By assuming that interfacial tension was absent and obtaining estimates of the gel viscosity from linear viscoelasticity data, KM found good quantitative agreement between the theoretical and experimental values of Γ for the range of gel-fluid thickness ratios (ratio 5) they investigated. Linear stability analyses have also been performed for finite Reynolds numbers and for pressure-driven flows through tubes lined with a gel layer [6][7][8][9]. While a weakly nonlinear analysis has been carried out which shows that the instability is subcritical [10], we are not aware of theoretical work exploring the strongly nonlinear regime of the instability.…”
Section: Introductionmentioning
confidence: 99%
“…By assuming that interfacial tension was absent and obtaining estimates of the gel viscosity from linear viscoelasticity data, KM found good quantitative agreement between the theoretical and experimental values of Γ for the range of gel-fluid thickness ratios (ratio 5) they investigated. Linear stability analyses have also been performed for finite Reynolds numbers and for pressure-driven flows through tubes lined with a gel layer [6][7][8][9]. While a weakly nonlinear analysis has been carried out which shows that the instability is subcritical [10], we are not aware of theoretical work exploring the strongly nonlinear regime of the instability.…”
Section: Introductionmentioning
confidence: 99%
“…This trend is reversed for Re'50. Consequently, it is di$cult to predict from this result the shape of the neutral-stability curves for large values of n where there may exist other kinds of instabilities as was shown in the inviscid calculations of Kumaran (1996). Figure 11 shows the neutral-stability curves in the plane (k, Re) for di!erent values of .…”
Section: Stability Of Flow In Viscoelastic Tubesmentioning
confidence: 98%
“…At high Re, the rate of transport of energy due to the deformation work at the interface is the negative of the rate of transport of energy in the wall layer due to the Reynolds stress v P v V . Kumaran (1996) employed a di!erent model for the compliant wall, considered an inviscid #ow and developed a stability condition for both axisymmetric and azimuthally varying disturbances with high azimuthal wavenumbers. The application of this condition to the Hagen}Poiseuille #ow showed that the axisymmetric disturbance is stable while the azimuthally varying mode with high wavenumber may be unstable.…”
Section: The Present Problemmentioning
confidence: 99%
“…The lacunae involved in using a linearized elastic model were first pointed out by Gkanis & Kumar (2003) in the context of plane Couette flow past a deformable solid layer. Much of the earlier work in this subject were based on the linearized elastic model (Yeo & Dowling 1987;Yeo 1988;Yeo et al 1994;Lucey & Peake 2003;Kumaran 1995Kumaran , 1998aShankar & Kumaran 1999, and it is important to examine whether the predictions obtained using the linearized elastic model would be modified by using a more accurate nonlinear model. We will specifically address this issue at various points in this review.…”
Section: Continuum Models For Solid Deformationmentioning
confidence: 99%